Adaptation of Fusarium oxysporum and Fusarium dimerum to the specific aquatic environment provided by the water systems of hospitals. (1st June 2015) - Steinberg, Christian; Laurent, Julie; Edel-Hermann, Véronique; Barbezant, Marie; Sixt, Nathalie; Dalle, Frédéric; Aho, Serge; Bonnin, Alain; Hartemann, Philippe; Sautour, Marc
Abstract: Members of the Fusarium group were recently detected in water distribution systems of several hospitals in the world. An epidemiological investigation was conducted over 2 years in hospital buildings in Dijon and Nancy (France) and in non-hospital buildings in Dijon. The fungi were detected only within the water distribution systems of the hospital buildings and also, but at very low concentrations, in the urban water network of Nancy. All fungi were identified as Fusarium oxysporum species complex (FOSC) and Fusarium dimerum species complex (FDSC) by sequencing part of the translation elongation factor 1-alpha (TEF-1α) gene. Very low diversity was found in each complex, suggesting the existence of a clonal population for each. Density and heterogeneous distributions according to buildings and variability over time were explained by episodic detachments of parts of the colony from biofilms in the pipes. Isolates of these waterborne populations as well as soilborne isolates were tested for their ability to grow in liquid medium in the presence of increasing concentrations of sodium hypochlorite, copper sulfate, anti-corrosion pipe coating, at various temperatures (4°–42 °C) and on agar medium with amphotericin B and voriconazole. The waterborne isolates tolerated higher sodium hypochlorite and copper sulfate concentrations and temperatures than did soilborne isolates but did not show any specific resistance to fungicides. In addition, unlike waterborne isolates, soilborne isolates did not survive in water even supplemented with glucose, while the former developed in the soil as well as soilborne isolates. We concluded the existence of homogeneous populations of FOSC and FDSC common to all contaminated hospital sites. These populations are present at very low densities in natural waters, making them difficult to detect, but they are adapted to the specific conditions offered by the complex water systems of public hospitals in Dijon and Nancy and probably other localities in the world. Graphical abstract: Highlights: Specific populations of FOSC and FDSC adapted to hospital water distribution systems. Tolerance of waterborne Fusarium isolates to copper, sodium hypochlorite and high temperatures. Low natural density of the populations outside the hospital water distribution system. Same two homogeneous populations of FOSC and FDSC common to several hospital sites. Suggestions for generalized preventive prophylactic methods.